IMPLEMENTASI SANKSI TINDAKAN BERSIFAT PRIMUM REMEDIUM TERHADAP ANAK BERKONFLIK DENGAN HUKUM - Mashuril Anwar (Universitas Lampung, 2021)
Criminal sanctions are more popular than action sanctions at the application level. Action sanctions formulation is regulated in Articles 82 and 83 of the Juvenile Criminal Justice System Law, while criminal sanctions are the last resort. However, criminal sanctions are still the